The agreement of peer assessment and self-assessment of learning processes in problem-based learning. - Miller PJ (Journal of Physical Therapy Education (American Physical Therapy Association, Education Section))
Problem-based learning (PBL) has become a widely utilized curricular design in health care professional education. One of the principal features of PBL that distinguishes it from more conventional curricular models is that its outcome objectives emphasize the processes of learning as much as the content of learning. However, there is a lack of literature that addresses the assessment of learning processes in PBL. The purpose of this study was to determine the value of a multiple-measurement method of assessing a student's learning processes in small-group work in PBL case problems. For each of .six case problems utilized in an entry-level kinesiology course, students completed peer assessments and self-assessments of learning activities within the group setting. Intraclass correlation coefficients (ICCs) demonstrated poor to moderate agreement between peer assessments and self-assessments for the case problems, and in two cases the lack of between-group variance invalidated the use of the ICC In addition, there was no trend in the change in the level of agreement as the course progressed. The low level of agreement was related to the restricted range of scores that students assigned to themselves and their peers. Although this particular multiple-measurement format was not a valid method for assessing student learning processes, further study with the use of an alternative scoring system is indicated.